2016
DOI: 10.1590/1414-431x20165526
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated Pseudomonas aeruginosa inhibits hypoxia-induced pulmonary hypertension by preventing TGF-β1/Smad signaling

Abstract: Pseudomonas aeruginosa is one of the common colonizing bacteria of the human body and is an opportunistic pathogen frequently associated with respiratory infections. Inactivated P. aeruginosa (IPA) have a variety of biological effects against inflammation and allergy. Transforming growth factor-β (TGF-β) signaling plays a critical role in the regulation of cell growth, differentiation, and development in a wide range of biological systems. The present study was designed to investigate the effects of IPA on TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Of these extracellular cues, TGF-β1 has a predominant role [25]. TGF-β1 is a multifunctional cytokine, a potent inhibitor of epithelial cell repair, and an inducer of PF through regulating cell proliferation, growth, differentiation, and movement [26]. Smad family protein is the intracellular transduction molecule of TGF-β family reported to be involved in the modulation of cell proliferation and migration [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these extracellular cues, TGF-β1 has a predominant role [25]. TGF-β1 is a multifunctional cytokine, a potent inhibitor of epithelial cell repair, and an inducer of PF through regulating cell proliferation, growth, differentiation, and movement [26]. Smad family protein is the intracellular transduction molecule of TGF-β family reported to be involved in the modulation of cell proliferation and migration [27].…”
Section: Discussionmentioning
confidence: 99%
“…As a component of cytoskeleton, α-SMA is expressed by myofibroblasts, which are a heterogeneous population of highly profibrogenic cells; high levels indicate the progression of fibrosis with collagen deposition. In experimental studies on fibrosis, this interstitial marker is highly expressed a few days after induction of fibrosis [23,24].…”
Section: Groupmentioning
confidence: 99%
“…The overexpression of miR-542-3p significantly inhibited the activation of β-catenin and nuclear factor-κB signaling pathways that promote carcinogenesis [ 25 ]. TGF-β signaling pathway also plays a very critical role in regulating cell growth, differentiation, and development of biological systems [ 29 , 30 ]. TGF-β1 promotes tumor cell growth through the Smad-ILK signaling pathway by increasing Smad2/3 and ILK expression [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…JAG1 and ADAM10 are indispensable components of Notch signaling pathway, which were predicted as downstream targets of miR‐140‐5p in our analysis, suggesting that lack of miR‐140‐5p might promote the development of PAH by upregulation of JAG1 and ADAM10 genes and therefore activation of Notch3 cascade. In addition, activation of TGF‐beta1/Smad4 signaling promotes a proliferative PASMC phenotype and induces PAH in rat . We found that TGF‐betaR1 and smad4 were possible downstream targets of miR‐140‐5p, reduction in miR‐140‐5p in PAH might stimulate TGF‐beta1/Smad4 pathway by upregulating TGF‐betaR1 and smad4.…”
Section: Discussionmentioning
confidence: 99%